A history of Christian thought ; v. 3 - Gonzalez, Justo L. (Nashville, TN Abingdon, 1975)
Contents : v. 3 : From the Protestant Reformation to the twentieth century. Includes bibliographical references and index.
Keywords: Theology, doctrinal -- history -- modern period, 1500-